Identification of Isoklinal Folds Against the Effect of Sumateran Fault Force In Air Batu Village And Surrounding Merangin Jambi Geopark - Tobi Prayoga; Magdalena Ritonga (Jurnal IPTEK, 2022)
The Merangin area, in particular, has experienced several tectonic phases and stages of change in the direction of the regional structure. In addition, on this island found, rocks of the Paleozoic age, their unique tectonic, geological system and constituent rocks will produce fascinating geological reconstructions. The unique tectonic design and constituent stones will have an absorbing geological reconstruction. The research methods include literature review, field observations, measurements, and studio analysis. Based on the literature and the research location approach, the research area is located in the physiographic zone of the Sumatera fault. Based on field observations, it is known that the constituent rocks are sedimentary, pyroclastic materials and intrusive granite rocks. The formations that arrange these rocks are the Mengkarang formation (Permian), the Tantan granite formation (Jurassic-Cretaceous), and the Kasai Formation (Tertiary). The fault data that passes through the building is the Sumatran fault with the position of Strike/Dip N322°E/76°, Bearing N135°E, and Rake 36°. This regional fault resulted in ductile rocks being repeatedly folded with an orientation approaching West-East; this can be observed in one of the fold data with the general direction of flank 1 N2850E/440 and the general rule of side 2 N136°E/42°. The result of the analysis is an anticline; this anticline occurs repeatedly and is referred to as an isoclinal fold perpendicular to the orientation direction of the Sumatran Fault. The pattern and movement of those folds and faults are by following under the concept of the wrench fault, which states that the fault strongly influences the formation of folds. Those folds will be perpendicular to the fault pattern.